Political and Religious Aspects in the ≪Slavophiles≫ Perception in the Early 20th Century (A. A. Kireev, F. D. Samarin, D. N. Shipov) - Paromov Kirill (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
A. A. Kireev, F. D. Samarin, D. N. Shipov are perceived as the representatives of the Slavophile tradition of Russian thought. For A. A. Kireev and D. N. Shipov socio-ethical ideal was achieved simultaneously religious and political aspirations. For F. D. Samarin unity of the Church and social issues was a guarantee of «organic development» of Russia. These public ﬁgures assumed religious opportunities in the social environment. As for early Slavophiles, the idea of the Church approached with the idea of «true community». Salvation as the Church task was closer to the liberal idea. The social aspect has become mandatory in the views of the Church.